Stable convergence of conditional least squares estimators for supercritical continuous state and continuous time branching processes with immigration - Barczy, Mátyás (Journal of statistical planning and inference, 2025)
We prove stable convergence of conditional least squares estimators of drift parameters for supercritical continuous state and continuous time branching processes with immigration based on discrete time observations. •Supercritical continuous state and continuous time branching processes with immigration.•Conditional least squares estimators.•Stable convergence.